«Місто тихе, срібношате, колихане в колисці зір» (епітетні характеристики міста в українській поетичній мові ХХ століття) - Іваненко, І. (Культура слова, 2021)
У статті продемонстровано активність епітетизації образу місто в українській поетичній мові ХХ століття. Наголошено, що ця номінація поєднується з автологічними (прямими,
описовими) та металогічними (переносними, образно-оцінними) означеннями.
З’ясовано, що корпус популярних автологічних означень
формують характеристики розміру (велике, гігантське, маленьке), віку (нове, старе, давнє, древнє, молоде), розташованості щодо адміністративного центру (центральне, провінційне), віддаленості від місця перебування ліричного героя
(далеке, близьке), часу (ранішнє, вечірнє, нічне). Також традиційним для української поетичної мови є вживання номінації
місто та конкретних назв міст із присвійними займенниками
моє, наше.
Констатовано, що в металогічних епітетах до образу місто матеріально-предметний план поступається емоційно-експресивному, асоціативно-образний зміст переважає над
номінативним. У семантичній структурі таких конструкцій
домінують семи ‛візуальне сприйняття’, ‛аудіальне сприйняття’, ‛психологічне сприйняття’, ‛історична конотація’.
Підсумовано, що загалом епітетизація відбиває і реалістичний, і образно-символічний, філософсько-узагальнений зміст
означуваного образу. Місто – це водночас і географічний
об’єкт, і естетизований художній простір, в якому відбувається самоідентифікація ліричних героїв. The noun city is an actively epithetized image of Ukrainian
poetry of the twentieth century. Around it are definitions with direct,
descriptive meaning (autological) and with figurative, figurativeevaluative
(metalogical). Autologous definitions include characteristics
of size (large, giant, small), age (new, old, ancient, ancient, ancient,
eternal, young), location relative to the administrative center (central,
provincial), distance from the location of the lyrical hero. close), time
(morning, evening, night).
Also traditional for the Ukrainian poetic language is the use of the
nomination city and specific names of cities with epithets beautiful,
abandoned, unfamiliar, with possessive pronouns my, our.
In many epithets to the image of the city material-subject plan is
inferior to the emotional-expressive, metaphorical, associative-figurative
word usage prevails over the direct, nominative. The semantic structure
of such constructions is dominated by seven ‘visual perception’, ‘audio
perception’, ‘psychological perception’, ‘historical assessment’.
Among the artistic definitions with the sema ‘visual perception’ the
most branched color-epithet series - white, yellow, green, blue, gray,
gray, black, gold. Carriers with a color sign (golden-topped, silverhaired,
white-winged) are carriers of complicated semantics and value.
The aesthetics of definitions with the dominant family ‘psychological
perception’ (suffering, torn, exhausted, tired, tragic, etc.) is determined
by their imagery and emotional coloring.
Anthropomorphic epithets transfer to the image of the city signs of psychoemotional
states (fatigue, suffering), character traits (pride, tenderness,
kindness, insecurity), morality or immorality (innocence, sinfulness), as well
as external portrait traits or signs of human physical condition.
Characteristic epithet microparadigms develop realities that
structure the city space, specify its social and cultural infrastructure.
In general, epithetization reflects both realistic and figurativesymbolic,
philosophical-generalized meaning of the image of the city.
It is both a geographical object and an aestheticized artistic space in
which lyrical heroes self-identify. Such a complex nature of the image
opens up prospects for its broad interpretation.